2018
DOI: 10.1016/j.jfda.2017.12.006
|View full text |Cite
|
Sign up to set email alerts
|

Synergic effect of curcumin and its structural analogue (Monoacetylcurcumin) on anti-influenza virus infection

Abstract: Curcumin (Cur), a polyphenolic compound extracted from spice and common food colourant turmeric, contains versatile bio-activities. Monoacetylcurcumin (MAC), a structural analogue of Cur, differs from Cur by acetyl modification, but retains enone groups. Comparative analysis revealed MAC effectively inhibited influenza virus infection (IAV) to a similar extent as, if not superior to, curcumin. Both compounds mildly reduced viral NA activity. Surprisingly, unlike Cur, the MAC inhibition of IAV did not occur thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
58
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(60 citation statements)
references
References 28 publications
2
58
0
Order By: Relevance
“…Thus, exploring novel strategies and/or the use of safe and effective natural products represents an urgent need to combat viruses . Curcumin has shown antiviral activity against numerous viruses including dengue virus (serotype 2), human immunodeficiency virus, Japanese encephalitis virus, pseudorabies virus, vaccinia virus, parainfluenza virus type 3 (PIV‐3), feline infectious peritonitis virus (FIPV), vesicular stomatitis virus (VSV), herpes simplex virus (HSV), flock house virus (FHV), respiratory syncytial virus (RSV), hepatitis viruses, influenza type A virus (IAV), Ebola virus, and arthropod‐borne viruses . Different possible mechanisms have been reported for curcumin's antiviral properties such as functioning as an HIV‐1 integrase inhibitor , degrading viral Tat protein , inhibiting proteases , inhibiting viral entry , inhibiting virus attachment to cells , and inhibiting viral replication .…”
Section: Antiviral Activitymentioning
confidence: 99%
“…Thus, exploring novel strategies and/or the use of safe and effective natural products represents an urgent need to combat viruses . Curcumin has shown antiviral activity against numerous viruses including dengue virus (serotype 2), human immunodeficiency virus, Japanese encephalitis virus, pseudorabies virus, vaccinia virus, parainfluenza virus type 3 (PIV‐3), feline infectious peritonitis virus (FIPV), vesicular stomatitis virus (VSV), herpes simplex virus (HSV), flock house virus (FHV), respiratory syncytial virus (RSV), hepatitis viruses, influenza type A virus (IAV), Ebola virus, and arthropod‐borne viruses . Different possible mechanisms have been reported for curcumin's antiviral properties such as functioning as an HIV‐1 integrase inhibitor , degrading viral Tat protein , inhibiting proteases , inhibiting viral entry , inhibiting virus attachment to cells , and inhibiting viral replication .…”
Section: Antiviral Activitymentioning
confidence: 99%
“…Due to its versatile pharmacological properties, including anti-inflammatory, anti-tumor, and anti-oxidant activities (Maheshwari et al 2006;Anand et al 2007;Goel et al 2007), curcumin has attracted considerable interest. In particular, curcumin is reported to have anti-influenza virus activity by interfering with the cellular signaling pathways (such as Toll-like receptor2/4, p38/c-Jun N-terminal kinase, mitogen-activated protein kinase, and nuclear factor-κB pathways) or with proteins required for influenza virus replication (Dai et al 2018;Richart et al 2018). Ou et al (2013) reported that the presence of the double bonds in the central seven-carbon chain enhances the curcumin-dependent anti-IAV activity and curcumin might interfere with IAV entry by its interaction with the receptor binding region of hemagglutinin.…”
Section: Introductionmentioning
confidence: 99%
“…Unequal synthetic pigments or dyes such as carmoisine and tartrazine that may macerate liver function and rise oxidative stress. Thus, these natural dyes are used not only as coloring for foods but also as a substance that boosts the health by preventing or healing many diseases [9].…”
Section: Introductionmentioning
confidence: 99%